2008
DOI: 10.1080/13880200701735031
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Liquid Chromatography Characterization and Identification of Antioxidant Polyphenols in Maple Syrup

Abstract: Maple syrup of four grades (extra-light, light, medium, and dark) of the 2007 crop was provided by three local (St. Joseph's Island, Ontario, Canada) producers. Twenty-four phenolic compounds were isolated from a medium-grade syrup and identified on the basis of spectral and chemical evidence. They were (a) benzoic acid and several hydroxylated and methoxylated derivatives (gallic acid, 1-Ogalloyl-β-D-glucose, γ -resorcylic acid); (b) cinnamic acid derivatives (p-coumaric acid, 4-methoxycinnamic acid, caffeic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 10 publications
3
49
0
Order By: Relevance
“…Furthermore, gallic acid and flavonoids were major polyphenols in plants in the Fagaceae family, which contribute to antioxidant activity [41,42]. Similar to the Betulaceae and Fagaceae, Aceraceae species were reported to exhibit antioxidant activity due to various phenolic compounds, such as quercetin, kaempferol, and flavonoid derivatives [43]. These results suggested that the relatively high contents of bioactive compounds in Aceraceae, Betulaceae, and Fagaceae might contribute to the high bioactivity of those families.…”
Section: Correlation Of Metabolic Differences and Bioactivities In Plmentioning
confidence: 77%
“…Furthermore, gallic acid and flavonoids were major polyphenols in plants in the Fagaceae family, which contribute to antioxidant activity [41,42]. Similar to the Betulaceae and Fagaceae, Aceraceae species were reported to exhibit antioxidant activity due to various phenolic compounds, such as quercetin, kaempferol, and flavonoid derivatives [43]. These results suggested that the relatively high contents of bioactive compounds in Aceraceae, Betulaceae, and Fagaceae might contribute to the high bioactivity of those families.…”
Section: Correlation Of Metabolic Differences and Bioactivities In Plmentioning
confidence: 77%
“…Maple syrup is produced primarily in North America with the vast majority of the world's supply coming from Canada (85%; primarily Quebec), followed by United States (Perkins & van der Berg, 2009). Previous reports have shown that maple syrup contains a wide variety of phenolic phytochemicals (Abou-Zaid, Nozzolillo, Tonon, Coppens, & Lombardo, 2008;Filipie & Underwood, 1964;Kermasha, Goetghebeur, & Dumont, 1995;Li & Seeram, 2010;Potter & Fagerson, 1992), which may have positive effects on human health. Recently, phenolic-enriched extracts of maple syrup were shown to have antioxidant, anti-mutagenic and human cancer cell anti-proliferative properties (Legault, Girard-Lalancette, Grenon, Dussault, & Pichette, 2010;Li & Seeram, 2010;Theriault, Caillet, Kermasha, & Lacroix, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…Previous reports have shown that maple syrup contains a wide variety of phenolic phytochemicals (11)(12)(13), which may have positive effects on human health, including potential for type 2 diabetes management via inhibition of the carbohydrate hydrolyzing enzyme α-glucosidase (7).…”
Section: Introductionmentioning
confidence: 99%